Distribution of bone morphogenetic protein receptors in human scleral fibroblasts cultured in vitro and human sclera - Zhen-Ya Gao; Li-Jun Huo; Dong-Mei Cui; Xiao Yang; Wen-Juan Wan; Jun-Wen Zeng (International Journal of Ophthalmology, 2012)
AIM: To investigate the distribution of bone morphogenetic protein receptors (BMPRs) in human scleral fibroblsasts (HSFs) and in human sclera. METHODS: Primary HSFs were cultured in vitro. The mRNA levels of BMP-2 and BMPRs in HSFs were assayed by reverse transcription-polymerase chain reaction (RT-PCR). The protein distributions of BMP-2 and BMPRs in HSFs were further detected by immunocytofluorescence and western blot. Their protein expression was also detected in frozen human posterior scleral sections by immunohistofluorescence.RESULTS: BMP-2 and BMPRs were expressed in both HSFs and human sclera not only at mRNA level but also at protein level. The expressions of BMPRIA and BMPRII were higher than that of BMPRIB in the cytoplasm and cell membrane of HSFs in vitro. Western blot further verified the results of immunocytofluorescence. In human sclera, BMP2, BMPR IB and BMPR II were found to be expressed in the cytomatrix of HSF, and weak signal was detected about BMPRIA.CONCLUSION: BMP-2 and all three subtypes of BMPRs were found in HSFs and may play a role in scleral remodeling.